(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Atrial fibrillation has emerged as a significant risk factor for ischemic stroke, and the use of direct-acting oral anticoagulants has been universally advised in stroke prevention. Nevertheless, in reality, the occurrence of a stroke has also been observed, mainly in the initial phase of anticoagulant initiation in patients with AF, and assessing the rate of stroke in newly treated patients. Objective: To establish that ischemic stroke often occurs in patients who have been newly diagnosed with atrial fibrillation and started on direct oral anticoagulants at a tertiary care hospital. Methods: This prospective observational study was conducted at the Emergency Department, Lady Reading Hospital, Peshawar, from January 2025 to June 2025. Consecutive sampling was used to enroll 150 adult patients with newly diagnosed non-valvular atrial fibrillation who were started on direct oral anticoagulants. Baseline demographic and clinical data of patients were recorded. Patients were followed up for four months, and the primary outcome was the occurrence of ischemic stroke, which was confirmed clinically and radiologically. The data were analyzed using descriptive statistics. Results: The participants had a mean age of 66.8 ± 9.7 years, and there was a predominance of male patients. Apixaban was the anticoagulant that was prescribed to most patients. There were 11 patients (7.3%) who developed ischemic stroke, with the majority of the cases happening during the first eight weeks of therapy. A greater number of stroke cases were found in patients with raised CHA₂DS₂-VASc scores, which points to the fact that these patients were always at risk of thromboembolism even though they were on anticoagulation. Conclusion: Ischemic stroke is always a very serious complication in the first period after the start of direct oral anticoagulants in patients with atrial fibrillation. Intensified early monitoring, personalized risk evaluation, and fine-tuning anticoagulant therapy may be some of the ways that can help reduce early stroke events in high-risk populations.